The effects of leadership, job satisfaction, and motivation on the performance of ASN employees in Wonocolo District - Herfianti, Fonnyta; Wardoyo, Dewie Tri Wijayati; Witjaksono, Andre Dwijanto (Seminar Nasional Manajemen, 2024)
This research seeks to evaluate the effects of leadership, job satisfaction, and motivation on the performance of ASN employees in Wonocolo District. A quantitative method was employed, using a survey with 150 employees participating as respondents. Data were collected via self-report questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that while leadership does not significantly impact employee motivation, it does have a significant effect on employee performance. Job satisfaction plays a significant role in influencing both motivation and performance. Moreover, motivation has a significant impact on employee performance. The study concludes that job satisfaction is a crucial factor in shaping employee motivation and performance. District leaders are encouraged to focus on boosting job satisfaction by fostering a supportive work environment, ensuring fair compensation, and offering career development opportunities. Future research should consider using mixed methods, incorporating additional variables, conducting longitudinal studies, and utilizing diverse data collection approaches for a more comprehensive understanding